2005
DOI: 10.1152/ajpheart.00406.2005
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic circadian clock within the cardiomyocyte

Abstract: Circadian clocks are intracellular molecular mechanisms that allow the cell to anticipate the time of day. We have previously reported that the intact rat heart expresses the major components of the circadian clock, of which its rhythmic expression in vivo is consistent with the operation of a fully functional clock mechanism. The present study exposes oscillations of circadian clock genes [brain and arylhydrocarbon receptor nuclear translocator-like protein 1 (bmal1), reverse strand of the c-erba␣ gene (rev-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
159
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(172 citation statements)
references
References 51 publications
7
159
0
Order By: Relevance
“…bmal1 and rev-erba␣). These oscillations exhibit a periodicity of between 20 and 24 h, with temporal patterns similar to those observed in the intact heart in vivo, consistent with the operation of a circadian clock within the cardiomyocyte (19).…”
supporting
confidence: 74%
See 2 more Smart Citations
“…bmal1 and rev-erba␣). These oscillations exhibit a periodicity of between 20 and 24 h, with temporal patterns similar to those observed in the intact heart in vivo, consistent with the operation of a circadian clock within the cardiomyocyte (19).…”
supporting
confidence: 74%
“…This molecular mechanism confers the selective advantage of anticipation, permitting the cell to respond rapidly to a given stimulus at the appropriate time of the day (24). Circadian clocks have been identified in a vast array of mammalian cell types, including components of the cardiovascular system (19,20,25,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the causal relationship between b-blockers and the clock system has not yet been clinically elucidated, it has been reported that norepinephrine influences the timing of the circadian clock within cardiomyocytes. 20 This means that the regulation of sympathetic neurotransmitters using b-blockers affects the clock system in cardiovascular cells. The b-blocker treatment affects not only physiological conditions but also transcriptional conditions, such as peripheral clock genes.…”
Section: Discussionmentioning
confidence: 99%
“…Almost every mammalian cell possesses an intrinsic circadian clock, a transcriptionally based molecular mechanism capable of regulating multiple cellular functions. In terms of the cardiovascular system, circadian clocks have been characterized within multiple cell types, including cardiomyocytes (7,42); however, little is known regarding the influence of intramyocellular circadian clocks on cardiovascular physiology and pathophysiology. This is particularly relevant, given the possibility that impairment of the circadian clock within the cardiomyocyte may significantly alter cardiac function, pathogenesis of cardiovascular disease (CVD), and/or treatment strategies during CVD states (e.g., chronopharmacology) (42).…”
mentioning
confidence: 99%